Correlation Risk Premia for Multi-Asset Equity Options - Matthias R. Fengler; Peter Schwendner (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
The lack of a liquid market for implied correlations requires traders to estimate correlation matrices for pricing multi-asset equity options from historical data. To quantify the precision of these correlation estimates, we devise a block bootstrap procedure. The resulting bootstrap distributions are mapped on price distributions of three standard types of multi-asset options. ?Minimal? bid-ask spreads that reflect the risk from estimating the unknown correlations are quoted as quantiles of the price distributions. We discuss the influence of different market regimes and different payoff structures on the price distributions and on the the size of the resulting bid-ask spreads.
urn:nbn:de:kobv:11-10049898
Keywords: 330; Multi–Asset Options; Correlation Derivatives; Correlation Risk; Bid-Ask Spreads; Block Bootstrapping; Market Making; Equity Derivatives; Optionspreistheorie; Risikoprämie; Korrelation; Finanzderivat; Bootstrap-Verfahren; Theorie